Selection of GP. Mur antigen‐negative RBC for blood recipients with anti‐‘Mi a ’ records decreases transfusion reaction rates in Taiwan - Yang, C.‐A.; Lin, J.‐A.; Chang, C.‐W.; Wu, K.‐H.; Yeh, S.‐P.; Ho, C.‐M.; Chang, J.‐G. (Transfusion medicine (Oxford, England), 2016)
To evaluate the clinical significance of GP. Mur antigen-negative blood selection for transfusion in patients with anti-'Mi ' records. The GP. Mur RBC phenotype is prevalent (7·3%) in Taiwan. Antibodies against GP. Mur (anti-'Mi ') are identified in 1·24% of our population, and anti-'Mi ' screening using GP. Mur RBC has been routine for Taiwan's blood banks. However, due to the lack of commercial antibodies, only cross-matching was used to prevent transfusion of GP. Mur-positive blood to patients with anti-'Mi ' in most hospitals. There is still a risk of GP. Mur-positive RBC exposure and subsequent anti-'Mi '-related transfusion reactions. Since February 2014, GP. Mur antigen-negative RBCs identified by reaction with anti-'Mi '-positive serum were selected for blood recipients with anti-'Mi ' records. The transfusion reactions between January 2013 and January 2014 were compared with those that occurred between February 2014 and July 2015. The transfusion reaction rate was significantly higher in anti-'Mi '-positive blood recipients compared to total subjects receiving an RBC transfusion before GP. Mur-negative donor RBC selection. After antigen-negative RBC selection, the transfusion reaction frequency in subjects with anti-'Mi ' became similar to total blood recipients. IgG form anti-'Mi ' antibodies were present in all cases of probable anti-'Mi '-related transfusion reactions. The time required for anti-'Mi ' boosting after transfusion was around 4-21 days. Selection of GP. Mur-negative RBC for transfusion to patients with anti-'Mi ' records could decrease the rate of transfusion reaction and antibody boosting. This procedure should be incorporated into blood bank routines in areas where anti-'Mi ' is prevalent.